KEPERCAYAAN MASYARAKAT TERHADAP MASJID TIBAN DI WONOGIRI INDONESIA - Saifuddin Zuhri (Kopertais Wilayah X Jawa Tengah, 2023)
Mosque is the place of worship for Muslims as an attempt to get closer to Allah Subhanallahuwata'ala. In Duwet hamlet, Kepuhsari village Manyaran of Wonogiri there is Tiban Mosque where people believe if it is not only meant and aimed as whorsip place such as general mosques. People believe that this mosque stood before the village existed. The aim of this study is to know of how the people beliefs to Tiban mosque. The focus of this study pointing on problem related to social construction on Tiban mosque. The method of the study used was qualitative descriptive. The data collection technique used was in-depth interview. The sample collection in this study used was purposive sampling. The theory used in this study were social construction theory declared by Peter L. Berger and religion concept declared by Emile Durkheim. The study result show that people beliefs to Tiban mosque based on social construction that is people believe the Tiban mosque as a sacred place, many people visit the Tiban mosque to pray and there are rituals that are carried out by the community, namely the practice of praying expecting blessings at the Tiban mosque.